Conductometric Studies of the Complexation of Zn2+, Cu2+, Co2+, Ni2+ and Cd2+ with Schiff Base Ligand in Acetonitrile Solution - Payehghadr, Mahmood; Akbar Babaei, Ali; Saghatforoush, Lotfali (Asian Journal of Chemistry, 2010)
The complex-formation reactions between Cu2+, Zn2+, Co2+, Ni2+ and Cd2+ ions with 4-nitro-2- [(2-(2-pyridin-2-yl-ethyl-solphanil)ethylymino)methyl]phenol (PYTANO2) Schiff base ligand, has been studied by conductometric method in acetonitrile at various temperatures. Formation constants of the 1:1 and 1:2 (metal ion to ligand) complexes were evaluated from computer fitting of the molar conductance-mole ratio data at different temperatures and found that complexes to vary in the order of Ni2+ > Co2+ > Zn2+ > Cu2+ > Cd2+. The enthalpy and entropy changes of the complexation reaction were determined from the temperature dependence of the formation constants.